Squat and countermovement jump performance across a range of loads: a comparison between Smith machine and free weight execution modes in elite sprinters - Irineu Loturco; Michael McGuigan; Tomás T. Freitas; Fábio Nakamura; Daniel Boullosa; Pedro Valenzuela; Lucas A. Pereira; Fernando Pareja-Blanco (Biology of Sport, 2022)
The aims of this study were to: 1) provide and compare the height achieved during Smith machine (SM) and free weight (FW) loaded jumps executed over a wide spectrum of loads (40–120% of body mass [BM]); and 2) test the difference between loaded and unloaded squat jump (SJ) and countermovement jump (CMJ) attempts in ten highly trained male sprinters. On the first visit, athletes performed unloaded SJ and CMJ, loaded SJ with loads corresponding to 40, 60, 80, 100, and 120% BM, and loaded CMJ at 100% BM using an Olympic barbell (FW). On the second visit, they performed loaded SJ and CMJ tests under the same loading conditions on the SM device and,subsequently, a half-squat one-repetition maximum (1RM) assessment. The relative strength (RS = 1RM/BM) of the athletes was 2.54 ± 0.15. Loaded SJ performance was similar between SM and FW, and across all loading conditions. Differences in favour of CMJ (higher jump heights compared with SJ) were superior in the unloaded condition but decreased progressively as a function of loading. In summary, sprinters achieved similar SJ heights across a comprehensive range of loads, regardless of the execution mode (FW or SM). The positive effect of the countermovement on jump performance is progressively reduced with increasing load.